Liaison Old Age Psychiatry Service in a Medical Setting: Description of the Newcastle Clinical Service - E. B. Mukaetova-Ladinska; G. Cosker; M. Coppock; M. Henderson; Y. Ali Ashgar; A. Hill; A. Scully; D. Robinson; K. Sells; S. Brotherton; C. Lowthian (Nursing Research and Practice)
Liaison Old Age Psychiatry services (LOAP) have begun to emerge in the UK and further development of the service is supported by the latest health policies. Since qualitative and quantitative studies in this area are lacking, we have undertaken a detailed quantitative prospective review of referrals to the Newcastle LOAP to evaluate the clinical activity of the service. We report high referral rates and turnover for the LOAP service. Reasons for referral are diverse, ranging from requests for level of care and capacity assessments and transfer to other clinical services to management of behaviour, diagnosis, and treatment. We outline the value of a multidisciplinary model of LOAP activity, including the important role of the liaison nursing team, in providing a rapid response, screening, and followup of high number of clinical referrals to the service.